PENGARUH LOKASI, KUALITAS PELAYANAN DAN RETAIL BRAND LOYALTY TERHADAP KESETIAAN PELANGGAN TOKO CV. KAWANI SARANA PETUALANG - Broery Andrew Sihombing (E-Journal Graduate Unpar, 2014)
The objective of this research is to determine the effect of Location, Service Quality through Customer Satisfaction and Retail Brand Loyalty of CV. Kawani Sarana Petualang against Customer Loyalty, and to determine Customer Loyalty Rate of CV. Kawani Sarana Petualang.Primary data is collected from questionnaires spread to 123 customers of CV. Kawani Sarana Petualang as respondents. The writer used purposive sampling technique to choose the respondents.This research has five variables: independent variable (Store Location, Service Quality, and Retail Brand Loyalty), dependent variable (Customer Loyalty), and intervening variable (Customer Satisfaction). The writer used Structural Equation Modelling (SEM) as analytical tool with Lisrel 8.7. program. The result shows that Store Location doesn’t effect to Customer Loyalty significantly with , while Service Quality through Costumer Satisfaction with  and Retail Brand Loyalty  affect to Customer Loyalty significantly. It also shows that the highest t-value againts Customer Loayalty is Retail Brand Loyalty variable with the value of 5,15 compared with Store Location and Service Quality variable.Keywords: Retail Mix, Service Quality, Customer Satisfaction, Brand Equity, Customer Loyalty, Structural Equation Modelling (SEM)